Endothelial nitric oxide synthase is not necessary for the early phase of ischemic preconditioning in the mouse - Guo, Yiru (2008)
It has been proposed that constitutive expression of endothelial NO synthase (eNOS) protects against myocardial ischemia/reperfusion injury in the naive (unstressed) state and that eNOS plays a critical role in the early phase of ischemic preconditioning (PC). We addressed these issues using both a genetic approach (i.e., eNOS null [eNOS(−/−)]) mice and a pharmacologic approach (with the NOS inhibitor N(omega)-nitro-l-arginine [L-NA]). We found that in the nonpreconditioned state, both of the available strains of eNOS(−/−) mice (C57BL6 and B6129) exhibited infarct sizes similar to the corresponding wild-type (WT) mice (63.3±2.2% [group I, n = 15] vs. 59.7±1.4% [group VI, n = 10] of the risk region and 60.9±3.6% [group IX, n = 14] vs. 68.2±2.5% [group X, n = 9], respectively). When WT mice were preconditioned with either one or six cycles of 4-min coronary occlusion (O)/reperfusion (R) 10 min prior to the 30-min O, infarct size was markedly reduced (28.5±3.3% [group II, one O/R cycle, n = 10] and 19.7±2.6% [group III, six O/R cycles, n = 7] of the risk region, respectively), indicating the development of a robust early PC effect. In eNOS(−/−) mice preconditioned with the same protocol, the reduction in infarct size was similar (24.9±2.9% and 15.3±2.4% of the risk region, after one [group VII, n = 9] or six O/R cycles [group VIII, n = 10], respectively), indicating that the PC effect was intact. When WT mice were pretreated with L-NA 30 min before sham PC (group IV, n = 7) or PC (group V, six O/R cycles, n = 7), infarct size was not different from untreated control and PC groups. We conclude that, in the mouse, basal eNOS activity does not modulate infarct size in the nonpreconditioned state and is not necessary for the cardioprotective effects of early PC. Early PC is not eNOS-dependent, at least in this species.